PENGEMBANGAN BAHAN AJAR DIGITAL PADA MATA KULIAH PEMBELAJARAN BERBASIS KOMPUTER DIPRODI TEKNOLOGI PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MAKASSAR - Maharani; Nurhikmah H; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research is a development research that produces a product so that it can improve quality, innovation and support the completeness of learning infrastructure using an R&D (Research and Development) approach. This study aims to 1) analyze the level of need for computer-based learning digital teaching materials, 2) determine the level of validity of computer-based learning digital teaching materials, 3) determine the practicality of computer-based learning digital teaching materials. This research was developed using a 4D model (Define, design, development, disseminate). The research was conducted in the Educational Technology program, Faculty of Education, Makassar State University. The subjects in this study were 2 validators, namely, content and media validators, 15 students of educational technology, and 1 lecturer who was influential in the subject. Collecting data using a needs identification questionnaire, content and construct validation questionnaire, media validation questionnaire, student response questionnaire and lecturer responses questionnaire. The results of content and media validation are in very good qualification. Practical trials were carried out with two user targets, namely the student's response was in very good qualification and the response of the influential lecturer was in the very good qualification as well. Based on the results of the analysis, it can be concluded that digital teaching materials for computer-based learning courses are valid and practical])